Estimates for the convergence rate in the limit theorem for extreme values of regenerative processes - Zakusylo, O. K.; Matsak , I. K. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 519.21We establish the rate of convergence to the exponential distribution in the general limit theorem for the extreme values of regenerative processes. We also suggest some applications of this result to birth and death processes and queue length processes.